Göttersöhne und Menschentöchter: Gen 6,1-4 als innerbiblische Schriftauslegung - Bührer, Walter (Zeitschrift für die alttestamentliche Wissenschaft, 2011)
Literary analysis of Gen 6,1-4 and study of its reception history (Part I) establishes that the narrative is a literary unity, with its terminus post quem given by the Priestly and remaining non-Priestly texts in the primeval history and its terminus ante quem by its use in the Aramaic Book of Enoch. In the history of redaction (Part II) Gen 6,1-4 is attributed to the redactor who combined the two literary strands of the primeval history together. By the composition of this myth he sought to answer the question raised in Gen 3,22 but never answered elsewhere, about the upper limit of humans’ lifespan, on the basis of the 120 years derived from the Moses tradition. The tradition about sexual relations between gods and humans from the entire ancient Near East was known to this redactor, but not in the form of a parallel narrative to Gen 6,1-4 (Part III).